2020
DOI: 10.1002/mnfr.201901105
|View full text |Cite
|
Sign up to set email alerts
|

Pork Meat Proteins Alter Gut Microbiota and Lipid Metabolism Genes in the Colon of Adaptive Immune‐Deficient Mice

Abstract: Scope: Excessive consumption of processed meat has been linked to an increasing risk of gut diseases. It is investigated how pork meat proteins affect colon homeostasis between normal and immune-compromised mice. Methods and results: Immune-deficient mice (Rag1 −/− ) and wild-type mice are fed a diet that contains 20% casein or protein isolated from cooked pork or dry-cured pork for 3 months. Rag1 −/− mice show greater variations in transcriptome responses and higher microbial diversity than wild-type mice aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…Pork industry is currently facing the big challenges of feeding sustainability and the unhealthy image of fat. In fact, pork production is about 38% of the total amount of meat produced in the world, being is the most commonly consumed meat in different European, American, and Asian countries [ 1 ]. Moreover, the combination between rise of global population and the increase in income, will double the overall demand for animal-derived products by 2050, including pork [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pork industry is currently facing the big challenges of feeding sustainability and the unhealthy image of fat. In fact, pork production is about 38% of the total amount of meat produced in the world, being is the most commonly consumed meat in different European, American, and Asian countries [ 1 ]. Moreover, the combination between rise of global population and the increase in income, will double the overall demand for animal-derived products by 2050, including pork [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“… 38 In mice, a portion of undigested Mb reportedly reaches the colon after meat intake. 39 A high-risk colon cancer group reportedly had a fecal pH of 7.0–8.0. 40 Therefore, the high AcAld formation in the meat and the Mb reactions at pH 7.4 may be related to both gastric and colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] However, previous studies showed that intake of pork meat protein diets induced colonic oxidative stress and low‐grade inflammation in immune‐deficient mice (Rag1 −/− ) under short‐term dietary intervention. [ 19 ] In addition, processed meat protein induced inflammation and hepatic lipogenesis by upregulating Nrf2/Keap1 signaling pathway in Glrx‐deficient mice fed for three months. [ 18 ] The differences between the present study and the previous study could be attributed to the balances between oxidative stress and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] In addition, processed meat proteins altered fecal microbiota composition in Glrx‐deficient mice [ 18 ] and affected colon health in both wild‐type and adaptive immune‐deficient mice by altering the gut microbiome profile. [ 19 ] The composition of mouse fecal microbiota varied dynamically with the feeding time of processed meat protein, in which the relative abundance of Bacteroidales S24−7 was observed to increase from 4 to 8 months of feeding, whereas the relative abundances of Rikenellaceae RC9 gut , Akkermansia, Alistipes, Clostridiales vadinBB60 , Clostridium sensustricto 1, and Anaerotruncus were dramatically reduced. [ 20 ] Gut microbiota has been shown to be associated with obesity, inflammatory diseases, and neuronal disorders.…”
Section: Introductionmentioning
confidence: 99%